Microplastic hotspots mapped across the Southern Ocean reveal areas of potential ecological impact - Aidan Hunter; Sally E. Thorpe; Arlie H. McCarthy; Clara Manno (Scientific Reports)
Abstract Marine microplastic is pervasive, polluting the remotest ecosystems including the Southern Ocean. Since this region is already undergoing climatic changes, the additional stress of microplastic pollution on the ecosystem should not be considered in isolation. We identify potential hotspot areas of ecological impact from a spatial overlap analysis of multiple data sets to understand where marine biota are likely to interact with local microplastic emissions (from ship traffic and human populations associated with scientific research and tourism). Then we account for cumulative effects by identifying which areas with potential elevated microplastic-biota interaction are already subject to climate change related stresses (ocean warming and acidification). Our analysis indicates that biologically productive coastal areas in proximity to populated facilities are where microplastics pose most risk to the ecosystem, and that the northern Antarctic Peninsula is likely to be the main risk hotspot. This study is the first to map the threat of microplastics to the Southern Ocean ecosystem in a multi-stressor context, locating where microplastic monitoring programmes and mitigation measures may be considered a matter of urgency.